Senggani Fruit Anthocyanins (Melastoma Malabathricum Auct, Non Linn) As Bacterial Dyes Differential Painting Techniques - Indrawati, Ratih; Ratnawati, Gervacia Jenny; Tumpuk, Sri (Politeknik Negeri Ujung Pandang, 2022)
Bacteria are difficult to see with a light microscope, because they do not absorb or refract light. Dyes absorb and refract light so that the contrast of bacteria with their surroundings is enhanced. Anthocyanins are water-soluble pigments that are naturally found in various types of plants. As the name implies, this pigment gives color to flowers, fruits, and leaves of green plants.This research is a type of descriptive research. The treatment consisted of painting bacterial preparations with anthocyanin pigment extract of senggani fruit with 70% ethanol solvent and control with gram staining. The treatments were: T1: staining of bacterial preparations with gram staining, T2: painting of bacterial preparations with anthocyanin extract of senggani fruit added with 14% citric acid as a substitute for safranin and NH4Cl as a substitute for crystal violet. The results of the study showed that anthocyanin pigment extract was proven to be used as a dye for Staphylococcus aureus, Escereria coli as a substitute for synthetic dyes Safranin and Crystal violet in Gram staining.